Identification of single nucleotide polymorphisms in sheep Mx genes: A premature stop codon abolishes Mx2 protein expression but did not affect fertility and early animal development - Cindy Eunhee Lee; Nahideh Moradi; Brad Hine; Nicholas M. Andronicos; Jody McNally; Jian-Wei Liu; Tanja Strive; Ina Smith; Peter W. Hunt; Michael Frese (PLoS ONE, 2026)
Mx proteins are interferon-induced GTPases that inhibit a wide range of viruses. The loss of functional Mx genes in mice and other model species is associated with inferior innate immune responses and increased virus susceptibility. Here, we describe genetic variations in the Mx genes of sheep ( Ovis aries ). More than 700 single nucleotide polymorphisms within or adjacent to MX1 and MX2 were identified by analysing whole genome sequence data from 68 sheep, representing 43 breeds from 19 countries. Amongst those are two biologically significant variations in the ovine MX2 gene: a guanosine-to-adenosine transition that generates a stop at codon 166 (c.497G > A; p.W166*) and a single nucleotide deletion in codon 329 that creates a frameshift and a premature stop of translation eight codons later (c.985del; p.Q329Sfs7*). A subsequent genotyping of Australian Merino sheep identified animals with a stop codon at position 166 in two research flocks that have been kept as closed flocks since the 1970s. Immunoblotting, immunofluorescence and mass spectrometry assays show that animals homozygous for the defect do not express detectable amounts of Mx2 proteins, and quantitative PCR suggests that the premature stop codon destabilises Mx2 mRNA. Furthermore, we found that Mx2-negative ewes and rams are fertile and that Mx2-negative lambs are indistinguishable from heterozygotes and wild-type animals in appearance, birth weight and growth rate.